(untitled) (Avocetta, 2017)
Apart from its wide continental distribution in the Palaearctic, Nearctic and, partially, in the African and Indo-malayan regions, the Golden Eagle Aquila chrysaetos occurs also in the largest Mediterranean islands (Ferguson-Lees & Christie 2001). The largest population lives in Sardinia (57-70 pairs, Ruiu this volume), 32-37 pairs have been recorded in Corsica (Seguin et al. 1998) and 16-22 pairs of the A. c. homeyeri subspecies in Crete (Xirouchakis 2001). It has been also listed as vagrant in Cyprus and Malta (BirdLife International 2016), while it became extinct in the Balearics (Viada 2006) and in the Aegean and Ionian islands (Xirouchakis 2001). Presence and breeding in Sicily has been recorded since the early XIX century (e.g. Palazzotto 1801 in Massa 1985). More recently, research on the Golden Eagle in Sicily has been usually focused on breeding phenology and distribution during fieldwork for Regional Atlases of breeding birds (Massa 1985, Lo Valvo et al. 1993, AA.VV. 2008), as well as a subject of a PhD thesis and post-doc grant (Di Vittorio 2007, 2011). Such data originating from a specific conservation project in the Madonie Regional Park (Sarà et al. 2011) and allowed for some investigation on the species’ habitat preferences in the island (Di Vittorio & Sarà 2009, Di Vittorio & López López 2014). Habitat preference modelling showed how mean altitude and slope in the eagles territory are the most important topographic variables, together with the extension of open habitats (arable land and grasslands), to predict the occurrence of the Golden Eagle in Sicily. Actually, the species occupies most of the northern ridge of the island from west (Trapani mountains) to east (Peloritani Mts). Pairs living in the south-western Sicani Mts are connected to the main range in correspondence to the Palermo mountains, while pairs living on Etna are embedded bebetween the Nebrodi and Peloritani. The Golden Eagle has never been recorded breeding in the south-east corner of the island (Erei and Iblei Mts).